2004
DOI: 10.2466/pms.99.2.701-710
|View full text |Cite
|
Sign up to set email alerts
|

Strength Training Effects on Physical Conditioning and Instep Kick Kinematics in Young Amateur Soccer Players during Preseason

Abstract: The purpose of this study was to examine effects of lower limb strength training on physical conditioning and kinematic characteristics of instep kicking in 16 young amateur soccer players who participated in initial and final laboratory tests. In addition to their standard preseason soccer program, 8 players comprised the experimental group, who performed an 8-wk. strength-training program. Maximal and relative isometric force of the lower limbs were significantly improved. Moreover, toe and ankle linear velo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
26
0
1

Year Published

2010
2010
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(28 citation statements)
references
References 13 publications
1
26
0
1
Order By: Relevance
“…It is commonly reported in previous studies that different resistance training types have positive effects on the motor skills of footballers like speed (Brito et al 2014,Meylan and Malatesta 2009, Christou et al2006, strength (Brito et al 2014, Jay et al 2004, Christou et al2006, quickness (Meylan andMalatesta 2009, Christou et al2006), stamina (Helgerud et al 2001) and balance (Iacono et al 2016, Sever 2017, Taskin 2016, Yıldızer and Kirazci 2017. Contrary to this, when the limited studies investigating the effect of this type of training on the technical skills of footballers are examined, it was found that speed and jumping work applied during the season had a positive effect on kicking skills of footballers (marques et al 2013, Sedano et al 2009, Villarreal et al 2015, Haghighi et al 2012, Manolopoulos et al 2004.…”
Section: Discussionmentioning
confidence: 87%
“…It is commonly reported in previous studies that different resistance training types have positive effects on the motor skills of footballers like speed (Brito et al 2014,Meylan and Malatesta 2009, Christou et al2006, strength (Brito et al 2014, Jay et al 2004, Christou et al2006, quickness (Meylan andMalatesta 2009, Christou et al2006), stamina (Helgerud et al 2001) and balance (Iacono et al 2016, Sever 2017, Taskin 2016, Yıldızer and Kirazci 2017. Contrary to this, when the limited studies investigating the effect of this type of training on the technical skills of footballers are examined, it was found that speed and jumping work applied during the season had a positive effect on kicking skills of footballers (marques et al 2013, Sedano et al 2009, Villarreal et al 2015, Haghighi et al 2012, Manolopoulos et al 2004.…”
Section: Discussionmentioning
confidence: 87%
“…Indeed, with regard to male players the effects of strength training on kicking performance are elusive. Manolopoulos et al (2004), Perez-Gomez et al (2008) and Sedano Campo et al (2009) concluded that strength training focusing on the lower limbs can lead to improved kicking performance in soccer in terms of ball speed, but it takes time to transfer this to a specific activity. Several authors (Billot et al, 2010; Anderson and Dorge, 2011) have stated that the discrepancy between the findings of previous experiments may be explained by different research protocols such as differences in the length of training programs, the status of subjects, and training loads.…”
Section: Introductionmentioning
confidence: 99%
“…If we take a look at typical movement sequences in soccer (abrupt stops and changes of direction, quick sprints, ball kicking and explosive shots) makes it clear that depend on the stretch-shortening cycle (SSC) characteristics of the involved muscles (Manolopoulos et al, 2004). Such actions generate explosive release and impact in a repetitive manner use the SSC and require rapid force production and high power output.…”
Section: Introductionmentioning
confidence: 99%